Landlord attitudes to the private rented sector in Ireland: survey results. Issue 6 (18th August 2017) - Duffy, David; Kelleher, Caroline; Hughes, Annette
Abstract: The private rented sector (PRS) in Ireland has grown rapidly over the past decade. A significant element of this growth occurred post-2006 and may be attributed to issues associated with the housing boom and bust. As economic recovery gets underway, severe supply constraints have emerged, putting pressure on the PRS. This paper presents findings of a national survey of landlords undertaken at this time, the first of its kind in Ireland. Despite the current difficulties being experienced in the Irish rental market over 60 per cent of landlords intend to remain in the sector. The survey points to policy changes that could help provide a more stable rental market, for example, the provision of unfurnished accommodation and longer leases. With approximately one-third of landlords expressing the intention to leave, maintaining supply remains a key challenge for the sector.